The Correlation Between Resilience Levels and Disaster Preparedness Among Students at SMP Negeri 26 Jakarta Regarding Flood Disasters - Wahyu, Fakaruddin; Setiawan, Cahyadi; Hardi, Ode Sofyan (Jurnal Penelitian Geografi (JPG), 2024)
This study aims to explore the relationship between resilience levels and disaster preparedness. The research employs a descriptive quantitative method with a correlational approach. The study was conducted on 83 students of SMP Negeri 26 Jakarta who had experienced flooding. The findings show that the correlation coefficient is non-zero, indicating a relationship between resilience and disaster preparedness. This relationship is positive, with a correlation coefficient of 0.454, suggesting that higher resilience correlates with higher disaster preparedness. The resilience levels of students who experienced flooding were categorized as high to very high, which aligned with their disaster preparedness levels, predominantly categorized as ready to very ready. Keywords: Resilience; Disaster Preparedness; Correlation